2013
DOI: 10.1590/s1679-62252013005000010
|View full text |Cite
|
Sign up to set email alerts
|

Repeated stressors do not provoke habituation or accumulation of the stress response in the catfish Rhamdia quelen

Abstract: Fish repeatedly experience stressful situations under experimental and aquaculture conditions, even in their natural habitat. Fish submitted to sequential stressors can exhibit accumulation or habituation on its cortisol response. We posed a central question about the cortisol response profiles after exposure to successive acute stressors of a similar and different nature in Rhamdia quelen. We have shown that successive acute stressors delivered with 12-h, 48-h, and 1-week intervals provoked similar cortisol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Other species including Eurasian perch Perca fluviatillis Linnaeus, 1758 and rainbow trout Oncorhynchus mykiss Walbaum, 1792 showed habituation to mechanical stress after 8 weeks (60). In contrast, studies on catfish Rhamdia quelen Quoy and Gaimard, 1824 did not observe habituation after 3 weeks of exposure to mechanical stress (61). Thus, habituation to predatory presence in a time perspective, should be considered species specific.…”
Section: Discussionmentioning
confidence: 91%
“…Other species including Eurasian perch Perca fluviatillis Linnaeus, 1758 and rainbow trout Oncorhynchus mykiss Walbaum, 1792 showed habituation to mechanical stress after 8 weeks (60). In contrast, studies on catfish Rhamdia quelen Quoy and Gaimard, 1824 did not observe habituation after 3 weeks of exposure to mechanical stress (61). Thus, habituation to predatory presence in a time perspective, should be considered species specific.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Madaro and collaborators (2016b) showed that Atlantic salmon parr and postsmolts showed an attenuated cortisol response to a chasing protocol after being exposed just for a few days to the same stressor. This is not always the case, however, and in other studies with fish submitted to repeated stressors, the physiological response to stress after repeated or prolonged exposure was not reduced (Koakoski et al, 2013;Madaro et al, 2016a;Mugnier et al, 1998),…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…Any kind of habituation or sensitization would be of relevance to the assessment of the actual welfare status of the fish in a facility, since habituation ability is part of fish natural robustness against stress exposure (Noakes and Jones, 2012). Some data suggest that fish are able to habituate to certain stressors (Johansson et al, 2016;Madaro et al, 2016b) but not to others (Barcellos et al, 2006;Koakoski et al, 2013). The physiological capacity for habituation in fish seems to depend on the type of stressor, the severity and the species involved.…”
Section: Introductionmentioning
confidence: 99%
“…Under experimental conditions, fish are continually subjected to small levels of stress caused by daily feeding and tank cleaning activities, sampling for biometric measurements and verification of disease status. This sequence of stressors can lead to accumulation of response or habituation of cortisol levels (Koakoski et al., ) which remain low even after application of acute stress. Unlike the findings of this study, Jeney et al.…”
Section: Discussionmentioning
confidence: 99%